FINANCIAL MANAGEMENT CONCEPTS IN ISLAMIC EDUCATIONAL INSTITUTIONS: Khairul Anwar - Khairul Anwar (LPPM STIA Nusantara Sakti, 2022)
So far, there is an impression that finance is everything in advancing an educational institution. Without sufficient financial support, it is as if he cannot do much in advancing the educational institutions he leads. This is because they think that all efforts to advance education must be funded by money. Efforts to advance educational components without financial support seem to have stagnated halfway. At least, there are two things that cause great attention to finances; First , finance is a key determinant of the continuity and progress of educational institutions. This has the consequence that education reform or development programs can fail and fall apart if they are not supported by adequate finances. Second , it is usually very difficult to obtain large amounts of money, especially for newly established private educational institutions. Funds are closely related to trust ( accountability ). If you want to get funds from BP3/Community, Madrasah/School or Higher Education must have a good program, so that the community believes that these programs can run well and be useful. In another sense, educational institutions must convince the owner of the funds in the use of these funds. Islamic educational institutions really need to regulate ( manage ) the finances of their institutions. How can this Islamic educational institution move the finance so that it can be easily spent for effective and efficient financing? namely, with budgeting (budgeting), implementation involves accounting (implementation of the budget), and evaluation involves (the process of evaluating the achievement of targets).